Evaluation of CHROMagar™ Candida Plus chromogenic agar for the presumptive identification of Candida auris. (7th April 2022) - Tamura, Takashi; Alshahni, Mohamed Mahdi; Makimura, Koichi
Abstract: Skin colonization by the emerging pathogen Candida auris is common in outbreaks within medical settings. Culture‐based screening of patients is an effective management strategy to control the pathogen, and the newly developed CHROMagar™ Candida Plus medium is claimed to enable the presumptive identification of C. auris . Here, we evaluated the use of this medium with 63 C. auris strains comprising its four well‐established clades, as well as genetically related comparators, including species from the Metschnikowia clade. The colors and halos of both confluent growth and discrete colonies of all the tested strains were compared. It was found that on CHROMagar™ Candida Plus, C. auris formed characteristic white colonies with blue‐green halos that were more evident after 72 hr of incubation at 35°C than after 48 hr. However, distinguishing between closely related species such as Candida haemulonii, Candida pseudohaemulonii, and Candida duobushaemulonii required the consideration of parameters other than color, including colony size and growth ability at 35°C. In conclusion, the novel chromogenic medium CHROMagar™ Candida Plus constitutes an easy screening tool for C. auris .